Opportunities for predictive proteogenomic biomarkers of drug treatment sensitivity in epithelial ovarian cancer - Philips, Trudy J.; Erickson, Britt K.; Thomas, Stefani N. (Frontiers in Oncology, 2025)
Genomic analysis has played a significant role in the identification of driver mutations that are linked to disease progression and response to drug treatment in ovarian cancer. A prominent example is the stratification of epithelial ovarian cancer (EOC) patients with homologous recombination deficiency (HRD) characterized by mutations in DNA damage repair genes such as BRCA1/2 for treatment with PARP inhibitors. However, recent studies have shown that some epithelial ovarian tumors respond to PARP inhibitors irrespective of their HRD or BRCA mutation status. An exclusive focus on the genome overlooks the significant insight that can be gained from other biological analytes, including proteins, which carry out cellular functions. Proteogenomics is the integration of genomics, transcriptomics, epigenomics and proteomics data. This review paper provides novel insight into the role of proteogenomics as an analytical approach to identify predictive biomarkers of drug treatment response in epithelial ovarian cancer. Proteogenomic analysis can facilitate the identification of predictive biomarkers of drug treatment response, consequently greatly improving the stratification of patients with EOC for treatment towards a goal of personalized medicine.